Expanded choreography and history writing in the flesh : Independent dance artists claiming their past - Vedel, Karen (Nordic Theatre Studies, 2022)
This paper looks at artist driven initiatives in Denmark since the 1980s that have aimed to document, collect, and archive the remains of an art form otherwise deemed short-lived, ephemeral, and marginal to the history of the performing arts. Approached through recent dance history as well as dance and archival theory, it unpacks how dance artists have taken on the task to create platforms to allow for insights from the past to inform the present as well as the future. The discussion engages two examples, each of which belongs to a different archival paradigm, before investigating in more detail a still ongoing dance archival/(hi)story project initiated in 2018 by a group of choreographers and dancers whose concept of their craft is informed by an expanded notion of choreography. Facilitating platforms for transgenerational exchanges between dance artists, the project named Danish Dance Stories explores participatory formats for the sharing of tangible remains, documents, stories about dance and the lives of dancers as well as the corporeal transmission of choreographic material, training approaches, artistic philosophies, and proposals. It will be argued that in the project’s entanglement of the ephemeral with the remains, the stories and the embodied traces, dance history writing becomes an artistic project in itself.